An intersectional critique of nursing's efforts at organizing - Wesp, Linda (Nursing philosophy, 2024)
Nursing's efforts at organizing in the United States have encompassed various approaches to creating change at a systemic and political level, namely shared governance, professional associations, and nurse unions. The United States is currently experiencing the effects of an authoritarian sociopolitical agenda that has taken aim at our profession's ethic of providing equitable care for all people through legislation that bans gender-affirming care and abortions. Nursing is simultaneously experiencing a crisis of burnout and moral distress, as we navigate the everyday functions of a for-profit healthcare system under the Capitalocene. As we situate ourselves within these policies and practices of late-stage capitalism and an increasingly authoritarian nation-state, we are compelled to think deeply about how nursing is currently organizing ourselves. Our paper will explore the evolution of various forms of organizing through the lens of intersectionality, which offers a framework for considering the ways that power operates, creating a matrix of sociostructural processes that fuel injustice. Intersectionality also compels us to examine whether our organizing has resisted, or perpetuated, a matrix of oppression. We will conclude by offering examples of radical imagining for a future of nursing resistance, where our collective organizing has a greater impact and responsibility for dismantling the status quo to achieve justice and liberation.